(untitled) (Scientific journal of the Fergana State University, 2024)
Multilingualism has existed for a long time and has been of great importance in the development of mankind. Despite all these factors, little is known about it and there are many unexplored questions. This article makes an attempt to consider the essence of the concept of “multilingualism” and provides a review of the literature on this topic. Currently, a problem for theoretical and practical research is the lack of a precise definition of multilingualism. This can explain the relevance and choice of the topic. The work also describes two forms of multilingualism and related phenomena.